Long-Term Outcomes of Pharmacoinvasive Reperfusion Strategy Depending on the Choice of Thrombolytic Agent in ST-Segment Elevation Myocardial Infarction - A. V. Khripun; A. A. Kastanayan; M. V. Malevannyi; Y. V. Kulikovskikh (Столичная издательская компания, 2019)
There is limited information on the comparative results of using different thrombolytic drugs for pharmacoinvasive reperfusion in acute ST-segment elevation myocardial infarction (STEMI). There is special interest in comparing the efficacy of fibrin-selective and fibrin-non-selective thrombolytics.Aim. To study the prevalence of major adverse cardiovascular events and the status of patients who had STEMI and pharmacoinvasive reperfusion a year ago, depending on the choice of thrombolytic drug.Material and methods. 240 STEMI-patients undergoing pharmacoinvasive reperfusion (reference event) were divided into 4 groups depending on the choice of the thrombolytic drug (alteplase [group 1], teneteplase [group 2], fortetelizin [group 3], streptokinase [group 4]) as well as into 2 groups depending on the fibrin-specificity of thrombolytics. One year after the reference event the prevalence of major cardiovascular events (death, repeated myocardial infarction, stroke, repeated revascularization of the target vessel, and their combination) was assessed. Data of echocardiography and 24-hour ECG monitoring, indicis of rating scale of clinical state in patients with heart failure (RSCS, Mareev V.Y, 2000), results of determination of plasma N-terminal pro-B-type natriuretic peptide (NT-proBNP) and of six-minute walk test were also analyzed.Results. One year after the reference event, patients who received fibrin-selective thrombolytics (groups 1,2, 3) compared with patients treated with fibrin-non-selective drug (group 4) had a higher left ventricular ejection fraction (49.8±7.4% vs 47,4±6.8%; p=0.048), lower index of impaired local contractility (1.19 [1.06; 1.38] vs 1.25 [1.175; 1.5], p=0.029), an end-diastolic volume (1 39.1 ±28.6 ml vs 148.7±23.9 ml; p=0.027), the size of the left atrium (39.0±4.6 mm vs 41.1 ±3.1 mm, p=0.007 ), and insignificantly lower prevalence of atrial fibrillation (1.5% vs 6.7%, p=0.068). They also showed a lower prevalence of supraventricular tachycardia (4.5% vs 13.3%, p=0.049) and ventricular extrasystoles (54.5% vs 76.7%, p=0.022) as well as the daily number of ventricular extrasystoles (4.5 [0; 32.0] vs 34, 0 [2.25; 80.25], p=0.001) with more favorable gradations and indicators of heart rate variability. Statistically significantly lower NT-proBNP level (148 [1 20; 208.5] pg/ml vs 241 [189; 287] pg/ml; p=0.000) and chronic heart failure manifestation according to RSCS (p=0.033), as well as a longer distance in the six-minute walk test (p=0.000) were found in patients treated with fibrin-selective drugs. Statistically significant differences between groups 1, 2, 3 for the study period were not found. Significant differences in the prevalence of hard clinical endpoints (death, repeated myocardial infarction, stroke, repeated revascularization of the target artery) were not found in all groups.Conclusion. More favorable clinical, laboratory and instrumental parameters were found one year after STEMI and pharmacoinvasive reperfusion with fibrin-specific thrombolytic agents as compared with fibrin-non-specific thrombolytic. All groups had no statistically significant differences in the effect on hard clinical endpoints during the entire observation period.